Resorbable implants in orthopaedics and traumatology including bone substitutes: present and potential clinical applications - Carter, C. (Injury : international journal of the care of the injured, 2002)
Abstrakty v nemčine, francúzštine, taliančine, španielčine, japončine, ruštine - s. 94-131